FAKTOR KRIMINOGEN TERHADAP PENYIMPANGAN HUBUNGAN KERJA OLEH NOTARIS (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 771 K/PID/2018) - Refilianosa Ibrahim Reflus; Armansyah (Program Magister Ilmu Hukum Universitas Pancasila, 2021)
One of the professions in the legal field that is closely related to various sectors of life is a notary. With thedevelopment of the public service sector, the public's need for services will increase. This has an impact onimprovements in the notary services sector. The role of a notary in the service sector is as an official who isauthorized by the State to serve the public in the civil sector, especially in making authentic deeds. In the provisionsof Article 1 number 1 of Law Number 2 of 2014 concerning the Position of Notary (hereinafter referred to asUUJN), it states that Notaries are public officials who are authorized to make authentic deeds and have other powersas referred to in this Law or based on law. other. Notaries are public officials who carry out the profession inproviding legal services to the public. As a notary who understands the rule of law, he should be able to act inaccordance with a high legal awareness. However, in reality there are still notaries who act deviating from theirauthority and position. One of the frequent violations of the Criminal Code is embezzlement. The notary was provento have committed irregularities in the work relationship and committed embezzlement in accordance with theSupreme Court Decision Number 771 / K / Pid / 2018. Criminogenous factors in the criminal act of embezzlementby a Notary will be analyzed using Bio-Sociology Theory. This research uses empirical juridical methods bycompiling hypotheses based on primary, secondary and tertiary data. Notary Internal and External Factors asCriminogen Factors on the Crime of Embezzlement. Internal factors such as lack of obedience and the desire that comes from within the Notary to commit embezzlement. External factors that come from the environment, such as the encouragement of notary's economic needs. We can find out these factors earlier by conducting a series ofpsychological tests which are one of the conditions for the appointment of a Notary